Adult dietary fat intake and ovarian cancer risk. Issue 10 (5th September 2019) - Rice, Megan S.; Poole, Elizabeth M.; Willett, Walter C.; Tworoger, Shelley S.
Abstract : The association of dietary fat intake with ovarian cancer risk has been inconsistent across populations. We examined dietary fat intake, overall and by type and ovarian cancer risk in two prospective cohort studies. We assessed long‐term dietary fat intake among Nurses' Health Study (NHS) and NHSII participants using food frequency questionnaires administered every 2–4 years beginning in 1984 and 1991, respectively. We examined cumulative energy‐adjusted intake of total fat, specific types of fat (animal, vegetable, saturated, monounsaturated, polyunsaturated and trans fat) and cholesterol. We identified 700 ovarian cancer cases in NHS and 196 in NHSII with dietary information. Cox proportional hazards regression was used to estimate associations between intake and ovarian cancer risk. Dietary fat intake changed over time in both cohorts and was lower in NHS than NHSII. Higher cumulative average intakes of animal fat and cholesterol were significantly positively associated with risk of ovarian cancer in NHS (relative risk [RR] comparing extreme quartiles = 1.57, 95% CI: 1.20, 2.06 and 1.35, 95% CI: 1.08, 1.69, respectively), but not in NHSII. Other dietary fat sources were not clearly associated with risk in either population. We did not observe clear associations between dietary fat and ovarian cancer risk in two large prospective cohort studies. Abstract : What's new? The lack of prevention recommendations and early detection for ovarian cancer make identifying modifiable risk factors critical for reducing incidence and mortality. Although dietary fat has been suggested to alter ovarian cancer risk by increasing circulating estrogen levels, studies on dietary fat and ovarian cancer risk have yielded inconsistent results. In this analysis of data from two large, prospective cohorts, higher long‐term dietary intakes of animal fat and cholesterol were associated with increased ovarian cancer risk, but only in the older cohort. Further pooled studies are needed to assess factors that might modify this relationship, like menopausal status and histotype.